Profile of the Gang Amal Traditional Market in South Belitung West Banjarmasin District - Nurul Maulida Arifa; Syaharuddin Syaharuddin; Rusmaniah Rusmaniah; Fatwa Nur’aini; Syarifuddin Syarifuddin (Universitas Lambung Mangkurat, 2026)
Gang Amal Market is one of the traditional markets that is still actively operating in South Belitung Village, West Banjarmasin District. Its existence attracts attention because it is only about 50 meters away from a modern market, namely a minimarket, even though South Kalimantan Provincial Regulation Number 12 of 2019 stipulates a minimum distance of 1 kilometer between traditional and modern markets. This situation raises questions about how Gang Amal Market has been able to survive and remain the choice of the community in meeting their daily needs. Nevertheless, Gang Amal Market remains in demand. This phenomenon shows that traditional markets are still surviving. The purpose of this study is to determine the profile of Gang Amal in Belitung Selatan Village, Banjarmasin Barat District. This study uses a qualitative method with data collection techniques through interviews, observation, and documentation. The results of the study show that Gang Amal Market has been operating since the 1990s and is still in demand by the local community and those from outside the area. This market is open from afternoon until night and offers a variety of food and non-food commodities, with product quality being a priority for traders. Social and cultural interactions are still maintained, and the market is managed independently.